2004
DOI: 10.1007/s00330-003-1924-6
|View full text |Cite
|
Sign up to set email alerts
|

Suspected ureteral colic: plain film and sonography vs unenhanced helical CT. A prospective study in 66 patients

Abstract: The aim of this study was to compare the sensitivity and specificity of plain abdominal films plus ultrasound, vs nonenhanced CT for the diagnosis of ureteral colic in patients with acute flank pain. During a 4-month period, 66 patients (mean age 48 years) with acute flank pain were prospectively studied by means of plain abdominal film, US, and unenhanced CT. The presence of lithiasis and of obstructive uropathy signs were determined. The plain film was only used as a guide for the US exam. Clinical follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 24 publications
8
94
1
7
Order By: Relevance
“…In the present study, the gray-scale Ultrasound sensitivity and specificity increased significantly when CDU was used with twinkling, where 99.6% of stones could be located with great confidence which is similar to results of recent studies (5,9). Regarding the echographic identification of ureterolithiasis, there are numerous studies with quite contradictory results and with a very wide range of values, the sensitivity of the method ranging between 19% and 96% (16)(17)(18). Our study showed the echographic identifications of ureteral calculi in 65.4% only.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the gray-scale Ultrasound sensitivity and specificity increased significantly when CDU was used with twinkling, where 99.6% of stones could be located with great confidence which is similar to results of recent studies (5,9). Regarding the echographic identification of ureterolithiasis, there are numerous studies with quite contradictory results and with a very wide range of values, the sensitivity of the method ranging between 19% and 96% (16)(17)(18). Our study showed the echographic identifications of ureteral calculi in 65.4% only.…”
Section: Discussionsupporting
confidence: 90%
“…Ultrasonography (US) is an imaging modality that may be used to investigate renal colic that does not expose the patient to radiation or contrast material. 19 Although reported estimates of the sensitivity of US to visualize ureteral calculi vary widely and are lower than that of CT (12%-93%), 20,21 US is highly accurate in detecting hydronephrosis, perinephric fluid and abnormal urinary jets, which often indicate the presence of calculi with sensitivity nearing 100%. 22,23 The specificity of US for direct or indirect findings compatible with ureterolithiasis is greater than 90% in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The specificity of US for direct or indirect findings compatible with ureterolithiasis is greater than 90% in some studies. 15,21,24 Additionally, US has been recognized as a useful imaging tool for patients in whom radiation exposure should be avoided. 25 The objective of this study was to determine the ability of US to identify renal colic patients with a low risk of requiring urologic intervention within 90 days of their initial ED visit.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] To determine the performance characteristics of the Verasonics imaging system, renal ultrasound images were obtained in nine human stone formers with 17 renal units. Ultrasound images of the upper, middle, lower poles, and the renal pelvis/UPJ were evaluated for stones by blinded reviewers and compared to recent CT imaging (within 60 days), which demonstrated a total of 27 stones with a mean size of 4.4 -3.3 mm.…”
Section: Sorensen Et Almentioning
confidence: 99%